A bifurcation result for equations with anisotropic p-Laplace-like operators. (4th October 2001) - Le, Vy Khoi
Abstract : The paper is concerned with a global bifurcation result for equations whose principal parts are anisotropicp -Laplace-like operators. Using an abstract bifurcation result for equations with multivalued operators in Banach spaces together with topological degree calculations, we show the Rabinowitz alternative for the bifurcating branches.